"Breaking Free" from the Frame: International Human Rights and the New York Times' 360-Degree Video Journalism. Issue 3 (15th March 2020) - Palmer, Lindsay
Abstract: This article conducts a qualitative textual analysis of the New York Times' 360-degree news reports that focus on international human rights issues, posing the following research questions: (1) How do the form and content of the New York Times' 360-degree videos potentially help to construct the vividness and interactivity that virtual reality scholars say will contribute to a greater sense of telepresence? (2) In what ways do the form and content of the New York Times' 360-degree video news reports reflect the tension between traditional notions of journalistic authority on the one hand, and the need to engage—on both ethical and economic levels—with news audiences on the other hand? The article will show that the news industry's deep ambivalence toward giving up control of the journalistic narrative in the digital age is coded into the visual and aural structures of the videos, raising questions about the celebratory discourse on agency and interpersonal engagement with distant suffering.